Speaking Anxiety in EFL Classrooms: Case of Second-Year LMD Students at University of Ghardaia, Algeria (Revue El-Wahat pour les Recherches et les Etudes, 2025)
This study attempts to investigate the sources of provoking English speaking anxiety among university students. The data were collected through a close-ended questionnaire completed by 40 students randomly selected from the Department of English at University of Ghardaia during the academic year 2021 – 2022.  The findings reveal that all Second Year (LMD) EFL Students experience some level of speech anxiety, even those who denied the fact of being anxious when it is needed to speak in class. Moreover, the main common anxiety-provoking situations for the students were performing in front of the classmates, giving an oral presentation and talking to teachers.The main reasons that led students to be anxious when they speak English in classrooms include the fear of being the center of attention, the lack of preparation, immediate error correction, and comparing oneself with other classmates. The paper concludes with some pedagogical implications for English language instructors who wish to reduce speaking anxiety in EFL classrooms.Keywords: Speaking anxiety, LMD students, gender, EFL, higher education